Figure skaters: Open and closed moments of inertia - Cochran, G. (1996)
1) Head contributes less than 5% to the fixed moment of inertia. The torso clearly dominates. 2) For the same length, the leg has twice the effect as a single arm. Both arms are about equivalent to the single right leg. 3) Although the leg is 4x the weight of the arm, they can both develop the same moment of inertia hanging straight down. This follows because the arm is attached at twice the distance from the spin axis as the leg. Don`t let the arm hang straight down in closure. 4) Everything scales. A small skater has the same ratio of moments of inertia as a large skater. This means size is not important. Body shape could be. This will have to be considered at a later time.